SOSIALISASI PENGGUNAAN APLIKASI CANVA UNTUK MENINGKATKAN KREATIVITAS SISWA DI SMP NEGERI 4 BAUBAU - Wa Ode Husniah; Susiana, Susiana; Nikmat, Atun; Nurfiana, Nurfiana; Al Zawari, Rafikal; Nur Hasan, Rezkiani (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM Azramedia Indonesia, 2024)
In this era of globalization, technology has a huge impact on various aspects of life, including aspects of education. Systems, tools, and all things related to the realm of education are increasingly tied to the name technology. Education also plays an increasingly large role in educational progress, including ease of access to materials, technology-based education systems, effective and efficient teaching tools and media, and others. Apart from that, technological developments have introduced many applications that make it easier for educators and students to receive and disseminate information, as well as in assignments. Canva is an online application that really helps all parties, including beginners from various backgrounds and fields, to provide facilities in designing information media and assignments in an interesting way so that the process of disseminating information and assignment results is more aesthetic and effective.